2016
DOI: 10.5455/ijmsph.2016.08022016402
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of antenatal care services in periurban area of Aligarh

Abstract: Background: Utilization of antenatal care (ANC) services is poor in the peri-urban areas, causing increased maternal morbidity and mortality. Objective: (i) To determine the current status of utilization of ANC services and (ii) to asses factors affecting utilization of ANC services. Materials and Methods: A community-based cross-sectional study was conducted in peri-urban field practice area of urban health training center, J N Medical College, Aligarh, India. The data were collected by home visit using a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 5 publications
3
10
0
Order By: Relevance
“…Prevalence of antenatal care utilization was 62.8% (95%CI,60.9–64.6) in this study. This finding is consistent with finding of the study done in North Maharashtra (64.2%) [ 20 , 21 ]. The possible rational for this consistency might be due to the following reasons: Study participants were in similar condition with socio-demographic status, awareness level about antenatal care service,and common traditional practice promoting home treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Prevalence of antenatal care utilization was 62.8% (95%CI,60.9–64.6) in this study. This finding is consistent with finding of the study done in North Maharashtra (64.2%) [ 20 , 21 ]. The possible rational for this consistency might be due to the following reasons: Study participants were in similar condition with socio-demographic status, awareness level about antenatal care service,and common traditional practice promoting home treatment.…”
Section: Discussionsupporting
confidence: 93%
“…According to this finding, antenatal care service was more utilized by women of rich wealth index than women in poorest wealth quintile. This finding is supported by findings of previous studies [26,29,32]. The possible rational for this similarities might be that antenatal care utilization need both direct and indirect cost.…”
Section: Discussionsupporting
confidence: 90%
“…15,17,24,32,37 In this study early ANC Registration during first trimester were found to be (p=0.000) significant factors associated with full utilization of ANC services than those who registered late in antenatal period. This was consistent with finding of studies conducted by Roy et al and Kushwaha et al 15,38 Encouraging early registration will ensure better maternal health in a long run.…”
Section: Discussionsupporting
confidence: 91%
“…This was not found consistent with other studies where tradition was found main reason for not having institutional delivery in studies of Kushwaha .This difference may be due to different population setting. [7][8][9][10][11][12] Present study shows the most common cause for no vaccination of child was that they don't feel necessary to vaccinate their child (42%). This was consistent with the study done by Mahajan H et al that also found no felt need as the main reason for low utilization of vaccination services (35.8%).…”
Section: Discussionmentioning
confidence: 99%